2010
DOI: 10.3109/08990220903574378
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immobilization of the head and trunk on arm-cycling-induced depression of soleus motoneuron pool excitability

Abstract: The purpose of this study was to investigate the effects of immobilization of the head and trunk on arm-cycling-induced depression of leg motoneuron pool excitability. Seven healthy humans participated in this study. The subjects sat on a chair with or without immobilization of the head and trunk. The subjects rhythmically cycled a crank of the ergometer with their hands at a frequency of 1 Hz. Soleus H-reflexes were evoked during arm cycling and during stational arm position. The H-reflexes were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Aruin and Latash (60) found that when humans perform voluntary arm movement, postural equilibrium suffers because of limb and body geometry changes, reflecting a postural adjustment. Based on these findings, Hiraoka and Taniguchi (61) explored if immobilization of the neck and trunk on arm-cycling induced depression of leg motoneuron pool excitability. They found that the H-reflex depression during arm cycling in the nonimmobilized condition was significantly larger than in the immobilized condition, suggesting a relationship between neck and trunk posture during arm cycling performance.…”
Section: Discussionmentioning
confidence: 99%
“…Aruin and Latash (60) found that when humans perform voluntary arm movement, postural equilibrium suffers because of limb and body geometry changes, reflecting a postural adjustment. Based on these findings, Hiraoka and Taniguchi (61) explored if immobilization of the neck and trunk on arm-cycling induced depression of leg motoneuron pool excitability. They found that the H-reflex depression during arm cycling in the nonimmobilized condition was significantly larger than in the immobilized condition, suggesting a relationship between neck and trunk posture during arm cycling performance.…”
Section: Discussionmentioning
confidence: 99%
“…Feet and arms were attached to the pedals and separate handles with Velcro strips. Trunk movements were not restricted, since it has been demonstrated that neural interlimb coupling is more pronounced with unrestricted head and trunk movements (12).…”
Section: Methodsmentioning
confidence: 99%
“…Splint immobilization of the forearm is performed in clinical practice for various indications such as post contusion, laceration, sprain, fracture, dislocation, luxation, and inflammation thereby reducing pain and spasms, decreasing swelling and inflammatory response, preventing further tissue damage and facilitating proper healing. In the past, studies focused on immobilization induced effects on osteoblast function and bone mineral content (Jaworski et al, 1980; Jozsa et al, 1988; Kuhr et al, 1982), tendon structure and tendon to bone interface (Aro et al, ; Hettrich et al, ; Nakamae et al, ), muscle content and intramuscular connective tissue morphology (Jozsa et al, ; Homma et al, ), cartilage and collagen turnover (Amiel et al, ; Ghosh et al, ; Sawamura et al, ), and neuromuscular response (Clark et al, ; Hiraoka and Taniguchi, ). By contrast, there are limited data of effects induced by immobilization on the human skin.…”
Section: Introductionmentioning
confidence: 99%